Multicultural Approach in Islamic Religious Education Curriculum as an Effort to Strengthen Content of Tolerance and Religious Moderation - Siregar, Bahtiar; Agustia, Nanda Rahayu; Harahap, Abdi Syahrial (Fitrah: Journal of Islamic Education, 2025)
Indonesia, as a multicultural country, faces serious challenges in maintaining social cohesion due to the increasing potential for conflicts based on intolerance. Islamic Religious Education, which has tended to be normative, is considered to be less than optimal in fostering religious moderation. This study aims to analyze the development of Islamic Religious Education materials based on multicultural values to strengthen religious tolerance and moderation, as well as to examine the role of teachers and school culture. The research uses a qualitative approach with a multisite study design at Panca Budi High School and Darussalam High School. Data collection was conducted through observation, in-depth interviews, and document studies. The results show that the integration of multicultural values into the curriculum and Islamic Religious Education materials is carried out systematically by emphasizing the social dimensions of Islam and applying contextual and dialogical learning strategies. Teachers act as agents of moderation who build an inclusive classroom climate, supported by a school culture that affirms the value of diversity through institutional policies and practices. These findings reinforce multicultural education theory and offer a model for developing an Islamic Religious Education curriculum that is adaptive to the realities of a pluralistic society and relevant to teachers and education policymakers.